تأثير كفاءة قراءة القرآن على مهارة الكلام بمدرسة البهجة القرآنيّة الإسلامية الثانوية شربون - Aziz, Umar Abdul (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2023)
Arabic is an absolute source and requirement that must be mastered in the pronunciation of reading the Qur'an. The source of the problem is the limited ability of a Muslim to read the Qur'an due to not mastering Arabic. The purpose of this study is to determine the effect of the efficiency of pronouncing makhraj letters in reading the Qur'an on the efficiency of pronouncing sounds in the speaking ability of eleventh grade students of SMAIQu Al-Bahjah Cirebon. This study uses the Expost Factor Quantitative method with the type of causal research (correlation research), which is useful research to determine whether there is a relationship between several variables. The data collection technique used by giving oral ability tests to students consists of oral tests of reading the Qur'an and oral tests of Arabic speaking skills. Meanwhile, to analyze data related to problem formulation, researchers use a simple linear regression test. The results of this study are: The correlation of the results shows that there is a relationship or influence between the efficiency of pronunciation of letters in reading the Qur'an and the efficiency of pronunciation of sounds in the speech ability of eleventh grade students at SMAIQu Al-Bahjah Cirebon with a number of 0.57. The value of the correlation coefficient of 0.57 is in the interval 0.40-0.60, which, if interpreted, indicates a moderate